The effect of productive classroom talk and metacommunication on young children's oral communicative competence and subject matter knowledge: An intervention study in early childhood education. (April 2017) - van der Veen, Chiel; de Mey, Langha; van Kruistum, Claudia; van Oers, Bert
Abstract: The aim of the present study was to investigate the effect of productive classroom talk and metacommunication on the development of young children's oral communicative competence and subject matter knowledge. This study can be characterized as a quasi-experimental study with a pre-test-intervention-post-test design. A total of 21 teachers and 469 children participated in this study. 12 teachers were assigned to the intervention condition and participated in a Professional Development Program on productive classroom dialogue. Multilevel analyses of children's oral communicative competence pre- and post-test scores indicated that our intervention had a significant and moderate to large effect on the development of young children's oral communicative competence. No significant effects were found for children's subject matter knowledge. The results of this study suggest that dialogically organized classroom talk is more beneficial than non-dialogical classroom talk for the development of children's oral language skills. Highlights: Traditional classroom talk is teacher-steered, based on recitation and non-productive. Productive classroom dialogue gives children space to talk and think together. Fidelity of the intervention on productive classroom talk was high. Productive classroom dialogue supports children's oral communicative competence. Children's subject matter knowledge did not differ between conditions.